Understanding the Impact of Mold Position on Brass Casting Microstructure and Hardness : An Observational Study by Production Operators - Mirza Wibisono; Nyoman Jujur; Iwan Setyadi; Suryadi Suryadi; E.H. Muslim; Nandang S.; Joni Syah; P.S. Hadi; W.A. Giri; Tika Mustika; Krisna Adhtya; Arif Hidayat (Balai Besar Logam dan Mesin, 2023)
The observation material was produced through the casting process, with a solar-powered crucible melting furnace. The molds used in the observation process consist of two positions, namely vertical and horizontal. The cartridge brass produced is in accordance with the ASTM B36 C26000 material standard.The slab of brass has a better level of homogeniity than the horizontal mold. The size of the dendrite α grains is smaller due to the slow freezing of the molten metal, which makes the growth of new dendrite α grains. The casting solidification begins from the part of the metal in contact with the mold, that is when the heat from the molten metal is taken by the mold so that the part of the metal in contact with the mold cools down to the freezing point, where the nuclei of the crystals grow. The inside of the casting cools down more slowly than the outside, so the crystals grow from the original nucleus towards the inside of the casting and the crystal grains are long and columnar in shape, which is called columnar structure. The cooling rate is faster than the inside of the casting, so the outside is softer, compared to the inside, harder. By carefully managing the cooling rate, manufacturers can control the microstructure of cartridge brass cast in permanent molds. This allows them to tailor the mechanical properties and overall performance of the final product to meet specific application requirements.